Targeting Human C-Type Lectin-Like Molecule-1 (CLL1) with a Bispecific Antibody for Acute Myeloid Leukemia Immunotherapy - Lu, Hua (Angew Chem Int Ed Engl, 2014)
Acute myeloid leukemia (AML), the most common acute adult leukemia and the second most common pediatric leukemia, still has a poor prognosis. Human C-type lectin-like molecule-1 (CLL1) is a recently identified myeloid lineage restricted cell surface marker, which is overexpressed in over 90% of AML patient myeloid blasts and in leukemic stem cells. Here, we describe the synthesis of a novel bispecific antibody, αCLL1-αCD3, using the genetically encoded unnatural amino acid, p-acetylphenylalanine. The resulting αCLL1-αCD3 recruits cytotoxic T cells to CLL1 positive cells, and demonstrates potent and selective cytotoxicity against several human AML cell lines and primary AML patient-derived cells in vitro. Moreover, αCLL1-αCD3 treatment completely eliminates established tumors in an U937 AML cell line xenograft model. These results validate the clinical potential of CLL1 as an AML specific antigen for the generation of a novel immunotherapeutic for AML.